Embedded-structure template for electronic records affects patient note quality and management for emergency head injury patients: An observational pre and post comparison quality improvement study. Issue 40 (October 2016) - Sonoo, Tomohiro; Iwai, Satoshi; Inokuchi, Ryota; Gunshin, Masataka; Kitsuta, Yoichi; Nakajima, Susumu
Abstract : Abstract: Along with article-based checklists, structured template recording systems have been reported as useful to create more accurate clinical recording, but their contributions to the improvement of the quality of patient care have been controversial. An emergency department (ED) must manage many patients in a short time. Therefore, such a template might be especially useful, but few ED-based studies have examined such systems. A structured template produced according to widely used head injury guidelines was used by ED residents for head injury patients. The study was conducted by comparing each 6-month period before and after launching the system. The quality of the patient notes and factors recorded in the patient notes to support the head computed tomography (CT) performance were evaluated by medical students blinded to patient information. The subject patients were 188 and 177 in respective periods. The numbers of patient notes categorized as "CT indication cannot be determined" were significantly lower in the postintervention term (18% → 9.0%), which represents the patient note quality improvement. No difference was found in the rates of CT performance or CT skip without clearly recorded CT indication in the patient notes. The structured template functioned as a checklist to support residents in writing more appropriately recorded patient notes in the ED head injury patients. Such a template customized to each clinical condition can facilitate standardized patient management and can improve patient safety in the ED.